Children With Developmental Language Disorder Have an Auditory Verbal Statistical Learning Deficit: Evidence From an Online Measure. Issue 1 (2nd August 2019) - Lammertink, Imme; Boersma, Paul; Wijnen, Frank; Rispens, Judith
Abstract : Successful language use requires the ability to process nonadjacent dependencies (NADs) that occur in linguistic input. Learning such structural regularities seems therefore crucial for children, and researchers have indeed proposed that language problems in children with developmental language disorder (DLD), especially problems with grammar, are due to their decreased sensitivity to NADs. Because the evidence supporting this claim is scarce, we compared children with DLD ( n = 36; M age = 9.1 years) and without DLD ( n = 36; M age = 9.1 years) performing a learning task with NADs. Using response times as an online measure of learning NADs, we observed that participants with DLD were less sensitive to NADs than were typically developing peers. The confidence intervals of the effect, however, indicated that the effect was probably small in size. We discuss clinical and theoretical implications of the present study in light of this effect size. Open Practices: This article has been awarded Open Materials and Open Data badges. All data, materials, and analysis scripts for this study are publicly accessible via the Open Science Framework at https://osf.io/8a3yv . The study materials are also publicly available via the IRIS database at https://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :